Current status of human rabies prevention: remaining barriers to global biologics accessibility and disease elimination - Charles E. Rupprecht; Naseem Salahuddin (Taylor & Francis Group, 2019)
Introduction: Rabies is a serious, neglected tropical disease. Zoonotic agents are RNA viruses (Genus Lyssavirus, Family Rhabdoviridae), global in distribution. As an acute, progressive, incurable encephalitis, rabies has the highest case fatality of any infectious disease. Warm-blooded vertebrates are susceptible hosts. Major mammalian reservoirs include mesocarnivores and bats. Given wildlife perpetuation, rabies is not eradicable, but is preventable and controllable, especially under newly available international guidelines. Areas covered: Literature review over the past 5 years reveals development of sensitive, specific diagnostic tests and safe and highly effective human and veterinary vaccines. Yet, tens of thousands of human fatalities occur annually, usually in Africa and Asia, primarily after canine exposure. Human and domestic animal vaccination, before or after exposure, is the single greatest preventative strategy following a rabid animal bite. Expert opinion: Significant progress occurred during the twenty-first century regarding vaccine development, doses, and schedules. Remaining barriers to widespread rabies vaccination include an inter-related set of economic, cultural, social, educational, ecological and technological factors. A basic understanding of local and regional root causes of cases historically allows for broader accessibility to vaccination in a trans-disciplinary fashion to meet the global elimination of human rabies caused via dogs (GEHRD) by 2030.